Rancang Bangun Dan Implementasi Sistem Informasi Absensi Ekstrakurikuler Berbasis Web - Latiful Ikhsan; Umi Chotijah (Universitas Katolik Widya Karya Malang, 2024)
Extracurricular activities are an integral part of every educational institution throughout a year of learning. In the current era where information is demanded at an accelerated pace, this research aims to develop a web-based extracurricular attendance information system for SMP Muhammadiyah 8 Benjeng. The current extracurricular attendance system at SMP Muhammadiyah 8 Benjeng is manual, prompting the need for this research to construct a website-based information system to facilitate students, supervising teachers, and staff at SMP Muhammadiyah 8 Benjeng. The extracurricular website serves as a source of information for the school principal, class teachers, and extracurricular supervisors. It provides information about students participating in extracurricular activities, the schedule of extracurricular sessions, and generates attendance reports for students over a semester and a full academic year. The system is designed using the waterfall method, implemented through (PHP) and MySQL. This research has successfully created a web-based platform for the management of extracurricular attendance. It is anticipated that this system will offer support to stakeholders responsible for overseeing extracurricular activities.